Bilangan Kromatik Lokasi Graf kubik C_(n,2n,2n,n) untuk n=3 - Salde Ofera (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Let G=(V(G),E(G)) be a connected graph and c be a coloring of the graph G. Let ∏={S_1,S_2,...,S_k }, where S_i is the class of colors in G which is colored i with 1≤i≤k. The representation of v with respect to Π is called a color code, denoted c_Π (v) is a k-element ordered pair, that is, c_∏ (v)=(d(v,S_1 ),d(v,S_2 ),...,d(v,S_k )), where d(v,S_i )=min{d(v,x)∣x ϵ S_i } for 1≤i≤k. If each vertex in G has a different color code then c is called a location coloring. The minimum number of colors used in the location coloring of a graph G is called the Location chromatic number with